The inportance of ascitic fluid fibronectin, cholesterol and serum-ascites albumin gradient in the differential diagnosis of malignant and non-malignant ascites - Hasan KAYA; Mehmet GÜNDOĞDU; Ersin AKARSU; Nihat OKÇU; M. Derya ONUK; S. Başol TEKİN; İlhami İKA (Turkish Journal of Gastroenterology, 2019)
-